HEPATOBILIARY COMPLICATIONS OF PARENTERAL NUTRITION IN CHILDREN - R. F. Tepaev; A. N. Kiryanova; E. I. Ilyicheva (Union of pediatricians of Russia, 2013)
Parenteral nutrition allows adequately providing children's bodies with amino acids, carbohydrates, fats and energy required to maintain the baseline energy level and correct the preceding nutritive deficiency. Long-term parenteral nutrition is associated with hepatobiliary complications of varying severity - from transitory complications to lethal ones, caused by cholestasis. The article presents modern data on diagnostics, prevention and treatment of hepatobiliary complications of parenteral nutrition in children.